2017
DOI: 10.1155/2017/6510198
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 Ameliorates Cigarette Smoke-Induced Airway Fibrosis by Suppressing the TGF-β1/Smad Pathway In Vivo and In Vitro

Abstract: Small airway fibrosis is a key pathological process accompanying chronic obstructive pulmonary disease (COPD) and includes fibroblast/myofibroblast transdifferentiation and excessive extracellular matrix deposition. Ginsenoside Rg1, one of the main active ingredients of Panax ginseng, has been shown to exert an antifibrotic effect in many tissues. However, little is known about the underlying mechanism and whether ginsenoside Rg1 can exert an effect on small airway fibrosis. We investigated the anti-small airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 37 publications
5
39
0
Order By: Relevance
“…Ginsenoside Rg1 is the main active ingredient of the ginseng rhizome extract and has antiapoptotic, antioxidant, antiinflammatory, and neuroprotective functions [17][18][19]. In addition, studies show that ginsenoside Rg1 can alleviate liver fibrosis, chronic obstructive pulmonary disease, and [20][21][22]. Previous studies show that ginsenoside Rg1 combined with astragaloside IV can protect renal function, which may be related to antioxidant stress and inhibition of TGF-β1/Smads pathway [23].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rg1 is the main active ingredient of the ginseng rhizome extract and has antiapoptotic, antioxidant, antiinflammatory, and neuroprotective functions [17][18][19]. In addition, studies show that ginsenoside Rg1 can alleviate liver fibrosis, chronic obstructive pulmonary disease, and [20][21][22]. Previous studies show that ginsenoside Rg1 combined with astragaloside IV can protect renal function, which may be related to antioxidant stress and inhibition of TGF-β1/Smads pathway [23].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatoprotection through the modulation of the Keap1-Nrf2-ARE pathway in preclinical models; amelioration of cigarette smoke-induced lung fibrosis by the downregulation of TGF-b/Smad pathway in pulmonary fibroblasts and COPD rats; induction of neural differentiation of ADSC through the microRNA-124 signaling; improvement of d-gal-induced POF by increasing both antioxidamt pathways and FSH receptor protein expression. Gao et al, 2017;Guan et al, 2017;Dong et al, 2017;He et al, 2017 Rg2 4,8,10,14-pentamethyl-2,3,5,6,7,9,11,12,13,15,16, 4,8,10,14-pentamethyl-2,3,5,6,7,9,11,12,13,15,16,17dodecahydro-1H-cyclopenta[a]phenanthren-6-yl]oxy]-6-(hydroxymethyl)oxane-3,4,5-triol Prevention of sleep deprivation-induced cognitive impairment in mice by reducing oxidative stress in cortex and hippocampus; reduction of oxidative stress-induced damage in rat primary astrocytes through the upregulation of MAPK and Nrf2/ARE signaling; osteoblast differentiation, osteogenic stimulation and antioxidant effect in mouse proteoblastic MC3T3-E1 cells via the BMP-2/Runx2 signaling pathways. Lu et al, 2017;Jung et al, 2016;Siddiqi et al, 2014 Rb1 plasma levels vis-a-vis with a significant increase in compound K plasma levels compared to those eating an Asian diet (Wan et al, 2017).…”
Section: Pharmacokinetics Of Ginsengmentioning
confidence: 99%
“…Its proportion is the main criterion which determines the quality of P. ginseng . 10 Studies have reported that Ginsenoside Rg1 has a strong anti-oxidative and anti-fibrotic effect. 11 14 Astragaloside IV, a characteristic and active constituent of Radix Astragali , possesses many biological effects.…”
Section: Introductionmentioning
confidence: 99%